CONTAMINATION OF WATER WITH HELMINTH EGGS: A CASE STUDY OF SOURANI DAM LAKE-TARTUS GOVERNORATE - KANAAN AL-TAMEEMI; AMAL DAYOUB; MERVAT MAZLOOM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In view of the serious prevalence of helminth and ease of infection, our research focuses on the detection of the prevalence of helminth eggs in the Sourani Dam Lake (Tartus governorate) water reflecting the health services and environmental circumstances in this region. Methods: The study was carried out on water samples of AL-Sourani Dam Lake with the aim to investigate the quality of water from October 2015 to September 2016 and verify the existence of helminth eggs according to their characteristics. Results: Our results showed a presence of helminth eggs such as Ascaris lumbricoides, Taenia saginata, and Hymenolepis nana in water samples. The total prevalence was 1.57 egg/L. T. saginata eggs were the most prevalent, followed by the eggs of A. lumbricoides, while the eggs of H. nana were the least prevalent, especially in summer and autumn. Conclusion: Due to the presence of helminth eggs in samples, it is recommended that sewage treatment plants be established and that health awareness be increased to decrease their prevalence.